Income analysis of Pryer Boat Charts fisherman in Lamuru Village, Tellu Siattinge District, Bone Regency) - Risna, Risna; Tahang, Hamzah; Fakhriyyah, Sitti; Hasani, M. Chasyim; Amiluddin, Amiluddin (PONGGAWA : Journal of Fisheries Socio-Economic, 2024)
Thys  study aims to determine the income analysis of bagan cungkil fishermen in lamuru village, tellu siattinge sub-district, bone district and to determine the profit sharing system found in bagan cungkil fishermen in lamuru village, tellu siattinge sub-district, bone district. This research was conducted from June to July 2021 in Lamuru Village, Tellu Siatinge District, Bone Regency. The type of research used is a quantitative and qualitative approach with a survey method. The sampling technique used is the census method. As for the income analysis of bagan cungkil fishermen in Lamuru Village, Tellu Siattinge District, Bone Regency, it was carried out by calculating the total income consisting of 10 Bagan Cungkil business units in Lamuru Village, Tellu Siattinge District, Bone Regency with revenues of Rp. 30,372,680,000/year. The costs incurred were IDR 3,606,440,668. So that the income is Rp.26,766,239,332 or with an average of Rp.2,676,623,933/unit. The profit-sharing system in the Bagan Cungkil Business Unit in Lamuru Village, Tellu Siattinge District, Bone Regency is still based on the customs of the surrounding community, namely 50:50, where the ship owner gets 50% of the total income and the crew also gets 50% of income